Mapping Educational Disparities in Life-Cycle Consumption - Svend E. Hougaard Jensen; Sigurdur P. Olafsson; Thorsteinn Sigurdur Sveinsson; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper uses data taken from the tax returns of all Icelandic taxpayers in 2005-2019, a period that saw large changes in disposable income around the country's financial crisis in 2008, to plot the life-cycle path of consumption and income for different education groups and to estimate the level of consumption smoothing. We split households into three groups based on educational attainment: primary education, secondary school, and university. We find that the university educated engage in more consumption smoothing than those without a university degree. We also construct a measure for marginal propensity to consume (MPC) out of transitory income and find that the university educated tend to have a lower MPC than those with less education. This implies that investing in education is an investment not only in higher income and sometimes more fulfilling jobs but also a more stable standard of living. There is a corollary that a higher level of average education can be expected to reduce the magnitude of the business cycle through a lower multiplier.
Keywords: E21; E24; 330; education; consumption; inequality